(untitled) (Materiali di Estetica. Terza serie, 2017)
This study links one scandal with another: that of the Nazi genocide and the role of women as active collaborators. In the works of Stephan Hermlin, Hans Lebert, Bernhard Schlink, Lukas Hartmann and Helga Schneider these women are mentioned as witnesses in their own prosecution, for the sake of a present and a future capable of coming to terms with the violence. Not only do the authors highlight a pat hay of meaning in their actions, they also tend to apply leverage on our inevitably limited moral judgements by way of these “evil women”. The aim is not that of seeking forgiveness, but rather that of stimulating the elaboration of the “evil” that lies within every individual. The current author argues that the productivity of the aesthetic experience of the negative is, at least potentially, transformative. The widening of the conscience, in fact, boosts the possibility of discovering the processes that allow us to communicate with other human beings, in such a way that a person endowed with a capacity to make moral judgements is, by the same token, one that is harder to manipulate, as well as being more peaceful.